Answer:
(5,9)
Step-by-step explanation:
3y=4x+7
5y=4x+25
Subtract the two equations to eliminate x
5y=4x+25
-( 3y=4x+7)
------------------
2y = 0x +18
Divide by 2
2y/2 = 18/2
y =9
Now find x
3y = 4x+7
3*9 = 4x+7
27 = 4x+7
Subtract 7
20 = 4x
Divide 4
20/4 = 4x/4
5 =x
(5,9)
Answer:
Below
Step-by-step explanation:
here is the factored form of a quadratic equation :
f(x) = a ( x +/- n ) ( x +/- n )
We can just plug in what we know into this form :
f(x) = 2 ( x + 4 )( x + 1 )
If you were to plug this into desmos it will show you the graph!
Hope this helps!
Answer:
793.787 or 800
Step-by-step explanation: